Pattern Spread of Aquifer using Sounding Resistivity Method with Schlumberger Configuration in Dayu Gondangrejo Karanganyar - Ashari, Bugar; D, Darsono; D, Darmanto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2014)
The research on ground water survey by using geo-electric method Schlumberger was conducted at Dayu Village, Gondangrejo, Karanganyar. Geo-electric is one of the geo-physics method which learned about electrical current in or on the earth surface. The equipment used includes resistivitymeter, GPS (Global Position System), roll meter, hammer, electrodes, and cables. Thepurpose of this research is to determine the spread pattern of the aquifer, groundwater potential, the thickness and depth of the aquifer at Dayu Village. The thickness of the shallow aquifer in the area of Dayu is between 3 m to 12 m with a depth of less than 30 m, while the deep aquifer is having a depth of more than 30 m with thickness between 68.5 m up to more than 165.7m.Thereis a degradation of aquifer pattern from Jambu Village (West) to Mulyorejo Village (East).Inversely, we found an increase from Tanjung Lor Village (North) to Watudakon Village(south). Shallow aquifer that potentially contain much groundwater sources located in the village of Tanjung Kidul, Mulyorejo, Jambu, Kedung Ulo and Tanjung Lor. For deep aquiferispotentially found at Pucung village and Kedung Ulo village.